Prevalence of Fatty Liver in Duhok Governorate; a cross-sectional study - Ahmed, Jeen Shahab; Ghazi, Dezhwar Yahya; Salih, Hawar M.; Salih, Zaynab M. (South Eastern European Journal of Public Health, 2025)
Background and objectives: fatty liver disease has an estimated prevalence of around 30% worldwide. The gold-standard method for the diagnosis is by liver biopsy. Ultrasound imaging can be used as a screening tool for the disease since it is less invasive, more widely available, and acceptable. The method uses B-mood for the detection of the features of the disease. Methodology: This cross-sectional study was conducted in a duration of 3 months; Jan-10th, 2024 to March 10th, 2024. A total of 413 samples were collected. Sampling started with filling out a questionnaire followed by the performance of ultrasound using the B-mood. All the data were analyzed using SPSS. A P value of < 0.05 was regarded as statistically significant. Results: The prevalence of fatty liver was found to be 22% in the total sample. The prevalence was higher among males (32.8%) compared to females (20.1%). We found that 45.1% of patients with a history of diabetes had fatty liver on ultrasound (P < 0.0001). The prevalence of fatty liver was higher among males than females and among overweight and obese compared to other groups; P = 0.028 and 0.008, respectively. Conclusion: Fatty liver is a burden on the population. The prevalence of the disease keeps rising over time leading to an increase in morbidity and mortality. Ultrasound should be used widely as a screening tool for detection of fatty liver.